Moving FOCUS – The Fire Service Organizational Culture of Safety survey – From research to practice. (September 2020) - Davis, Andrea L.; Allen, Joseph; Shepler, Lauren; Resick, Christian; Lee, Jin; Marinucci, Richard; Taylor, Jennifer A.
Highlights: The FOCUS research to practice evolution may hold utility for other occupations. FOCUS has steadily moved occupational safety research to practice in the field. FOCUS is helping shift the fire service further upstream towards prevention. Culture Camps are building fire service confidence and competence with FOCUS data. Abstract: Introduction: FOCUS, the Fire Service Organizational Culture of Safety survey, has evolved from a research to practice enterprise within the United States fire and rescue service. The FOCUS tool was developed through a FEMA Assistance to Firefighters Research & Development grant. Then it moved to practice in the field. To date over 35, 000 firefighters have participated. A current FEMA Fire Prevention & Safety grant can support FOCUS assessment in up to 1, 000 fire departments, with the potential of nearly 120, 000 respondents. With each funding cycle, the goal of the FOCUS program is to grow and measure its research to practice impact. Methods: We describe how FOCUS safety culture results are disseminated to fire service stakeholders. By utilizing customized reports and a training curriculum we demonstrate how FOCUS is moving research to practice by: (1) illustrating how survey results can be delivered effectively to practitioners, (2) providing examples of how fire departments are using results, and (3) sharing the reactions of the fire service to the FOCUS instrument, reports, and our flagship data training curriculum – Culture Camp. Results' Conclusions: Qualitative and quantitative data are analyzed to demonstrate the impact and acceptance of the FOCUS report and Culture Camps. Stakeholders reflect on the report and the experience of having quantitative safety culture data. Culture Camps are evaluated qualitatively and quantitatively using a matching game exercise, pre/post-test, a fire department teach back, and a Qualtrics evaluation. Practical Applications: Traditionally, the fire service has focused on reducing negative safety outcomes. FOCUS is helping shift their attention further upstream in the prevention pathway through the measurement of important organizational outcomes. The research to practice evolution of the FOCUS program may hold utility for other occupational groups when considering how to steadily move occupational health and safety research to practice in the field for measurable impact.